Land Use Management Based on Community Movement Patterns in Pajukukang District, Bantaeng Regency - Despry Nur Annisa Ahmad; Ulfitasari Nur; AR Fuad Hasanuddin (JURNAL RUANG / ISSN : 2085-6962, 2026)
Traffic and transportation are two interrelated aspects. The movement of people toward activity centers impacts the transportation system, where the concentration of activities leads to a need for transportation infrastructure and facilities to support this movement. This study aims to analyze the generation and distribution from eight functional areas studied through interviews, documentation, and literature review with 300 respondents. The data collection was conducted over two days, including a holiday and a workday. The results of this study are findings showed that the travel movement generation and distribution from the 300 respondents amounted to 385 movements across different origin and destination zones. Based on the Origin-Destination Matrix, land use management in Pajukukang District designated Baruga Village as a trade and service zone as well as a public space zone, Papanloe Village as an industrial zone, Borongloe Village as a worship zone, and Pajukukang Village as a health, port, and educational zone.